Environmental principles : from political slogans to legal rules - Sadeleer, Nicolas de (Oxford : Oxford University Press, 2021)
With more states paying heed to environmental principles as catalysts for improving their environmental law, this book traces the evolution of environmental principles from their origins to their embodiment in enforceable laws. This edition will integrate to a greater extent the relationship between environmental principles and human rights.
Translated from the French.
This edition of this translation previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 15, 2020).
Keywords: Environmental law; Environmental law, International; Environmental policy; Law; Laws of specific jurisdictions & specific areas of law